ACUTE AND SUBCHRONIC TOXICITY EVALUATION OF THE ĐHHV HERBAL FORMULATION IN EXPERIMENTAL ANIMALS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the acute toxicity and subchronic oral toxicity of the ĐHHV herbal formulation in experimental animals.Methods: Acute oral toxicity was assessed in Swiss albino mice using the Litchfield–Wilcoxon method. Subchronic oral toxicity was evaluated in Wistar rats over 90 days following the guidelines of the World Health Organization (WHO) and the Vietnam Ministry of Health.Results: The median lethal dose (LD₅₀) of ĐHHV could not be determined at the highest tested dose of 120 g/kg in mice. In the 90-day subchronic toxicity study, general clinical observations, hematological parameters, biochemical indices, and histopathological findings of the liver and kidneys showed no significant differences between the control group and the two treatment groups (p > 0.05).Conclusion: The ĐHHV formulation appears safe in the acute toxicity assessment and at the administered doses in the 90-day subchronic oral toxicity study in rats.
Keywords: ĐHHV, acute toxicity, toxicity, subchronic toxicity.